Human Resource Management During the Spread of the Coronavirus (Covid – 19) Pandemic Situation - Panitchaikul, Paweena; Sucaromana, Umaporn; Sansang, Sansang (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2023)
This academic article aims to present concepts and methods for human resource management to respond to the Faculty of Science, Srinakharinwirot University's values during the spread of the Coronavirus (Covid-19) pandemic. The values of the Faculty of Science comprise 1) Sharing is the cooperation between personnel, including the organization's collaboration, 2) Caring is the care, supervision, and advice provided to students and staff members, focusing on social responsibility; and 3) Integrating is the integration of existing resources to enable development for the better. Such as integrating teaching, research, and academic services, trahsdisciplinarity through analyzing and synthesizing data from the Ministry of Public Health guidelines, the university announcement, the announcement of the Faculty of Science, and interviewing with personnel of the Faculty of Science. The results found that the Faculty of Science has concepts and methods for managing human resources during the Coronavirus (Covid-19) pandemic in 6 areas. All areas have been conducted via online channels as follows: 1) Human Resource Recruitment, when it is necessary to take the practice exam, it will be done through social distancing; 2) personnel training and development has developed training courses considering the suitability of the position and sent training courses to personnel via email; 3) employment rate management, this was found that the coordination was delayed, but the goal was still achieved and on schedule; 4) performance management and performance evaluation showed that personnel was more aware of self-development. Guidelines and operating manuals were prepared; 5) problem-solving and conflict reduction, there is a guideline for reimbursing the cost of infection testing. The faculties will directly coordinate with the agencies responsible for that matter; 6) caring for personnel after retirement or needing to resign from the government sector was as effective as face-to-face meetings as personnel could adapt to the situation.